2020
DOI: 10.3390/biomedicines9010009
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Effect of Inflammatory Stimuli and Characteristics of Tryptophan Transport on Brain Capillary Endothelial (TR-BBB) and Motor Neuron Like (NSC-34) Cell Lines

Abstract: Tryptophan plays a key role in several neurological and psychiatric disorders. In this study, we investigated the transport mechanisms of tryptophan in brain capillary endothelial (TR-BBB) cell lines and motor neuron-like (NSC-34) cell lines. The uptake of [3H]l-tryptophan was stereospecific, and concentration- and sodium-dependent in TR-BBB cell lines. Transporter inhibitors and several neuroprotective drugs inhibited [3H]l-tryptophan uptake by TR-BBB cell lines. Gabapentin and baclofen exerted a competitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…We hypothesize that the alteration in the expression of transporters in the presence of pro-inflammatory cytokines might be the reason for the reduction in the uptake of [ 3 H]L-lysine. As reported in a previous article, depending on the cell type, there is up- and down-regulation of transporter expression in the inflammatory state ( Gyawali and Kang, 2021a ). However, in the MT cell lines, co-treatment with L-lysine had a protective effect against pro-inflammatory cytokine states.…”
Section: Discussionsupporting
confidence: 59%
“…We hypothesize that the alteration in the expression of transporters in the presence of pro-inflammatory cytokines might be the reason for the reduction in the uptake of [ 3 H]L-lysine. As reported in a previous article, depending on the cell type, there is up- and down-regulation of transporter expression in the inflammatory state ( Gyawali and Kang, 2021a ). However, in the MT cell lines, co-treatment with L-lysine had a protective effect against pro-inflammatory cytokine states.…”
Section: Discussionsupporting
confidence: 59%
“…Other glucose transporters are also modulated, as another report has shown that LPS endotoxin enhanced GLUT3 [119]. Moreover, amino-acid transport at the BBB level suffers alteration in inflammatory states, as shown in a recent paper assessing the increase in tryptophan uptake by the transport mechanisms of tryptophan in brain capillary endothelial as an effect of neuroinflammation (LPS and TNF-α as main triggers) [120]. Another in vivo study [94] demonstrated the downregulation of L-type amino acid transporter 1 (LAT1) in inflammatory states, with the thyroid hormone passage being modulated similarly to other important biomolecules (adenosine, insulin) in neuroinflammation.…”
Section: 11 Alteration Of Ecs During Inflammationmentioning
confidence: 93%
“…ALS is linked to pathological features such as protein misfolding, impaired axonal transport, glutamate excitotoxicity, oxidative stress, endoplasmic reticulum (ER) stress, neuroinflammation, and mitochondrial dysfunction [3]. In SOD1 mutant models, essential transporters such as monocarboxylate transporters (MCTs), large neutral amino acid transporter 1 (LAT1), and organic cation/carnitine transporters 1 and 2 (OCTN1 and 2), are reportedly altered [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%